Gastrointestinal Cancers and Liver Cirrhosis: Implications on Treatments and Prognosis - Xiang, Ze; Li, Yiqi; Zhu, Chaojie; Hong, Tu; He, Xianglin; Zhu, Hua; Jiang, Danbin (Frontiers in Oncology, 2021)
Liver cirrhosis tends to increase the risk in the management of gastrointestinal tumors. Patients with gastrointestinal cancers and liver cirrhosis often have serious postoperative complications and poor prognosis after surgery. Multiple studies have shown that the stage of gastrointestinal cancers and the grade of cirrhosis can influence surgical options and postoperative complications. The higher the stage of cancer and the poorer the degree of cirrhosis, the less the surgical options and the higher the risk of postoperative complications. Therefore, in the treatment of patients with gastrointestinal cancer and liver cirrhosis, clinicians should comprehensively consider the cancer stage, cirrhosis grade, and possible postoperative complications. This review summarizes the treatment methods of patients with different gastrointestinal cancer complicated with liver cirrhosis.